2014
DOI: 10.1007/s10661-014-3701-1
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation water quality and the benefits of implementing good agricultural practices during tomato (Lycopersicum esculentum) production

Abstract: The implementation of good agricultural practices (GAP) from irrigation water to the tomato packaging process enhances the safety of fresh produce and its value throughout the food chain. The aim of the present study was to show that fresh produce farms that apply and enforce GAP could reduce the presence of Salmonella in finished produce. Samples were collected biweekly from six packing houses from the central region of Sinaloa, México, for the isolation of Salmonella spp by the ISO 6579:2002 method, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
13
0
3
Order By: Relevance
“…López-Cuevas et al (2009) found Salmonella Typhimurium, as well as Infantis, Anatum, Agona, Oranienburg, Minnesota in agricultural water in the Culiacan region. Similarly, Estrada-Acosta et al (2014) found Salmonella Oranienburg in the Culiacan river. These findings highlight the needs for microbial determination numbers to determine the impact of the pathogen in water.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…López-Cuevas et al (2009) found Salmonella Typhimurium, as well as Infantis, Anatum, Agona, Oranienburg, Minnesota in agricultural water in the Culiacan region. Similarly, Estrada-Acosta et al (2014) found Salmonella Oranienburg in the Culiacan river. These findings highlight the needs for microbial determination numbers to determine the impact of the pathogen in water.…”
Section: Resultsmentioning
confidence: 91%
“…Culiacan is the capital of Sinaloa and is located in the Northwestern part of Mexico. This particular region is rich in vegetable produce farms that export several crops to the United States each year, particularly tomatoes and bell peppers (CIAD, 2006;Estrada-Acosta et al, 2014). In an effort to examine microbial contamination in this region, a comprehensive study to determine the presence of bacterial pathogens and the identification of critical points during the production chain is needed.…”
mentioning
confidence: 99%
“…[3,8,10,15,29,[43][44][45][46][47][48] In addition, farmers and farm workers can contribute to contamination through improper hygiene and crop handling. [3,4,15,44,45,47,48] Irrigation water also plays an important role in the preharvest contamination of fresh produce [3][4][5] which may potentially transmit pathogenic microorganims, such as Shigella, Vibrio spp., pathogenic strains of Escherichia coli, rotaviruses, adenoviruses, and enteroviruses. [22,49,50] Detecting the presence of fecal indicator microorganisms is therefore important to assess potential levels of pathogenic microbial contamination in primary production environments.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of water and food contaminated with Salmonella are the main routes of infection for gastrointestinal diseases (López et al, ). At the same time, this pathogen has been characterized by its prevalence and high distribution in the environment, especially in aquatic environments, particularly in the rainy season by the contaminated drag effect of organic matter (Simental and Martinez‐Urtaza, ; Estrada‐Acosta et al, ; Jimenez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several Salmonella strains have been isolated and characterized from some Mexico’s water bodies, and the most prevalent serotypes found in these studies were Oranienburg and Saintpaul (Lopez‐Cuevas et al, ; Jimenez et al, ; Estrada‐Acosta et al, ; Jimenez et al, ). While these two serotypes are nontyphoidal strains, they have been linked to food‐borne outbreaks, at the global and national levels, mainly associated with the consumption of fruits and vegetables (CDC, ; Vazquez‐Garciduenas et al, ).…”
Section: Introductionmentioning
confidence: 99%